1996
DOI: 10.1104/pp.112.2.591
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aluminum-Resistance Mechanisms in Wheat (Roles of Root Apical Phosphate and Malate Exudation)

Abstract: Although it is well known that aluminum (AI) resistance in wheat (Trificum aestivum) is multigenic, physiological evidence for multiple mechanisms of AI resistance has not yet been documented. l h e role of root apical phosphate and malate exudation in AI resistance was investigated i n two wheat cultivars (AI-resistant Atlas and AI-sensitive Scout) and two near-isogenic lines (AI-resistant E13 and AI-sensitive ES3). I n Atlas AI resistance is multigenic, whereas in E13 resistance is conditioned by the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
3
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 20 publications
5
130
3
3
Order By: Relevance
“…The involvement of rhizosphere alkalinization (Degenhardt et al, 1998), efflux of Al from the symplasm (Ezaki et al, 1999), and decreased cell-surface negativity (Wagatsuma and Akiba, 1989) are also possible. There is evidence indicating that Al tolerance in PI 416937 involves three to five genes (Bianchi-Hall et al, 1998), which is consistent with concomitant operation of multiple Al-tolerance mechanisms, as evidently occurs in wheat (Pellet et al, 1996).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The involvement of rhizosphere alkalinization (Degenhardt et al, 1998), efflux of Al from the symplasm (Ezaki et al, 1999), and decreased cell-surface negativity (Wagatsuma and Akiba, 1989) are also possible. There is evidence indicating that Al tolerance in PI 416937 involves three to five genes (Bianchi-Hall et al, 1998), which is consistent with concomitant operation of multiple Al-tolerance mechanisms, as evidently occurs in wheat (Pellet et al, 1996).…”
Section: Discussionmentioning
confidence: 64%
“…Root tip Al concentrations were found to be lower in Al-tolerant genotypes with other plant species as well (Rincó n and Gonzalez, 1992;Tice et al, 1992;Delhaize et al, 1993a;Ryan et al, 1997;Samuels et al, 1997;Larsen et al, 1998). A myriad of processes could contribute to Al exclusion from the meristematic cell region, including increased secretion of mucilage (Horst et al, 1982;Crawford and Wilkens, 1997), polypeptides (Basu et al, 1999), inorganic phosphate (Pellet et al, 1996), and organic acids (Delhaize et al, 1993b;Basu et al, 1994;Delhaize and Ryan, 1995;Pellet et al, 1995;Larsen et al, 1998). The involvement of rhizosphere alkalinization (Degenhardt et al, 1998), efflux of Al from the symplasm (Ezaki et al, 1999), and decreased cell-surface negativity (Wagatsuma and Akiba, 1989) are also possible.…”
Section: Discussionmentioning
confidence: 99%
“…According to our estimates, the differences in PM surface negativity and AI sorptive capacity, whatever the cause of the latter, probably account for some of the difference in genotypic sensitivity to AI3+, but the greater part of that difference may arise because malate and phosphate secretion by cv Atlas root tips reduces the amount of AI3+ that can reach the PM (Huang et al, 1996;Pellet et al, 1996). The evidence that malate release is a general mechanism for tolerance in wheat is reasonably strong now.…”
Section: Discussionmentioning
confidence: 83%
“…Because plant anion channels can be regulated by a number of external and internal factors (Ebel and Cosio, 1994;Schroeder, 1995;Thomine et al, 1995;Ward et al, 1995), it is possible that at least in wheat and maize, Al may play a role in anion-channel gating (Delhaize et al, 1993b;Pellet et al, 1995Pellet et al, , 1996Ryan et al, 1995aRyan et al, , 1995b. Support for this possibility comes from the results of a recent study by Ryan et al (1997), which were based on an electrophysiological (patch-clamp) analysis of protoplasts isolated from the root apex of the Al-resistant wheat line used to initially demonstrate Al-inducible malate release.…”
Section: Organic Acid Exudation In Relation To Al Resistancementioning
confidence: 99%
“…More recently, it was shown that constitutive phosphate release might operate in conjunction with Al-induced organic release to confer a greater degree of Al resistance in certain wheat genotypes (Pellet et al, 1996). Another mechanism of Al exclusion that is frequently proposed is a root-mediated elevation in the pH of the rhizosphere adjacent to the root apex (Kochian, 1995).…”
mentioning
confidence: 99%